Metaverse’s communities on X/TWITTER - Bonales Daimiel, Gema; Liberal Ormaechea, Sheila; Ávila Muñoz, Raquel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
During the last months, the metaverse has grown its popularity mainly linked to the entertainment industry. This has led to the emergence of new influencers who have achieved a significant increase in their follower base. This study applies a mixed research methodology based on the analysis of X/Twitter. The main conclusion obtained is that it is growing very rapidly, primarily within specific user communities with advanced and highly specialized knowledge about specific topics, such as cryptocurrency enthusiasts or online gaming fans and before it becomes a mass phenomenon, it will need to be simplified for the general population usage.